Implementation of a structural monitoring network in the new stone masonry bridge in Vila Fria - Portugal - António Arêde (2006)
This paper reports on the case of a new stone masonry bridge fully instrumented for structuralmonitoring under service loading. Both the monitoring scope and the instrumentation actuallyinstalled are described for this singular type of new construction. The acquisition systems aswell as remote data transmission and archive are also addressed. Some preliminarymonitoring results are included.